Coal and Gas: the Two Pillars of Balancing the National Energy System of Poland by 2040 - Tokarski , Stanisław; Tajduś, Antoni; Szulc, Waldemar (Archives of Mining Sciences, 2026)
In 2025, the share of electricity from renewable sources in Poland exceeded 30% of the national energy mix. To maintain the stability of the national grid, the operator was forced during that period to reallocate a total of approximately 1 TWh of energy from weather-dependent sources. Restrictions on feeding energy into the grid during periods of overproduction are accompanied by rapid growth in new capacity from wind and solar power sources. An analysis of subsequent drafts of the National Energy and Climate Plan, as well as planning documents of the national grid operator PSE, indicates that despite ongoing investments, a significant capacity gap in controllable capacity may emerge in the national system after 2032. As a result of decisions in the capacity market, new gas-fired units have been contracted, whose capacity is to exceed 12 GW in 2030. Further gas projects are currently in the preparation phase; however, their attractiveness to investors depends solely on the 15-year revenue stream from the capacity market. At the same time, the national grid embraces hard coal and lignite-fired units that can continue operating beyond 2035 and provide controllable capacity to the system operator without the need for serious capital expenditures, and at a lower cost than new gas-fired units. Given the risks associated with the availability and price of imported natural gas, which stem from the escalation of regional conflicts, the guiding principle of the state’s energy strategy should be to balance the national grid using coal and natural gas during periods when energy from weather-dependent sources is unavailable. A roughly proportional share of these two fuels in filling the power gap and balancing the system until the first nuclear power plant is connected to the grid should ensure energy independence and resilience to regional energy crises.